2016
DOI: 10.1186/s12889-016-3185-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of healthy behaviors for metabolic syndrome among Korean adults: a modified information-motivation-behavioral skills with psychological distress

Abstract: BackgroundSince the worldwide incidence of metabolic syndrome (Mets) has rapidly increased, healthy behaviors such as weight control, engaging in physical activity, and healthy diet have been crucial in the management of Mets. The purpose of this study was to examine healthy behaviors practice and factors that affect the practice in relation to Mets on the basis of a modified Information-Motivation-Behavioral skills model (IMB) with psychological distress, which is a well-known factor affecting healthy behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 46 publications
0
34
1
1
Order By: Relevance
“…[ 37 ] In our study, risk perception did not increase in any of the adherence constructs. Given the high importance of risk perception in different studies[ 38 39 40 ] and their emphasis on the great impact of risk perception on the adherence to treatment, risk perception seems to be one of the effective factors on adherence. Therefore, health care providers to patients with HIV should be provided with specific information about the risks caused by nonadherence to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[ 37 ] In our study, risk perception did not increase in any of the adherence constructs. Given the high importance of risk perception in different studies[ 38 39 40 ] and their emphasis on the great impact of risk perception on the adherence to treatment, risk perception seems to be one of the effective factors on adherence. Therefore, health care providers to patients with HIV should be provided with specific information about the risks caused by nonadherence to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Second, there may be information bias due to using self-reported data to analyze associated factors of lifestyle modification. Third, we had limited information on other influencing factors, such as knowledge, motivation, social support, and self-efficacy [ 36 ], regarding MetS healthy lifestyles. Therefore, we had to obtain detailed information about dietary control and physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…This part of the questionnaire used the 21-item version of the OP Self-Efficacy Scale (OSES) [40], which was developed as a measure of self-efficacy (or confidence) in behaviors related to physical activity and calcium intake [41]. The instrument comprises an exercise subscale (items 1-10) and a calcium intake subscale (items [11][12][13][14][15][16][17][18][19][20][21]. The scoring method for the scale is an 11-point scoring method from 0 ("No Confidence At All") to 10 ("Full Confidence").…”
Section: Behavioral Skills: Self-efficacymentioning
confidence: 99%
“…Modification of health behaviors requires consideration of factors that influence healthy behaviors [16]. A previous qualitative study showed that pre-requisites for OP patients to adopt self-care behaviors included increasing their hope of living longer, physician's attention to the patient's needs, media promotion, and family support [17].…”
Section: Introductionmentioning
confidence: 99%